Prediction of school students’ mental health based on the variables of attitude toward school, social support and educational-career planning - Yadegari, Ahmad; Omidi, Maboud (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
the present study aims to predict school students’ mental health based on the variables of attitude toward school, social support and educational- career planning of Second high school first grade students in Hamedan province.